Cancer Biomarkers in Diagnosis and Therapeutics - Shehzad, Adeeb (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book illustrates the basics and underlying molecular machinery of cancer cells and biochemical assays that detect the type and stage of cancer through cell signaling biomarkers. It starts with a brief introduction to cancer biomarkers and addresses technologies for identifying and validating cancer biomarkers, biomarkers for cancer drug development, prognostic and diagnostic biomarkers, and microbiome as cancer biomarkers. It reviews predictive biomarkers for anticancer drugs, biomarkers in cancer survival and drug resistance, biomarkers in tumor recurrence and metastasis, the role of the biomarker in immunotherapy and personalized medicine, and the development of a novel cancer biomarker. Finally, this book also underpins the role of nanotechnology in the use and detection of cancer biomarkers for enhanced sensitivity and specificity. Lastly, it discusses the challenges with biomarkers in cancer drug discovery and development. This volume is an indispensable tool for researchers working in the field of cancer and also for clinical oncologists.
Chapter 1. Introduction to cancer biomarkers -- Chapter 2.Technologies for identification and validation of cancer biomarkers -- Chapter 3. BIOMARKERS FOR CANCER DRUG DEVELOPMENT -- Chapter 4. Clinical proteomics: diagnostics and prognostic markers of Cancer -- Chapter 5.Microbiome as cancer biomarkers -- Chapter 6. Predictive biomarkers for anticancer drugs -- Chapter 7. Biomarkers in Cancer Survival and Drug Resistance -- Chapter 8. Biomarkers in tumor recurrence and metastasis -- Chapter 9. Biomarkers for Cancer Immunotherapy -- Chapter 10. Role of Biomarkers in Personalized Medicine -- Chapter 11.Development of Novel Cancer Biomarkers for Diagnosis and Prognosis -- Chapter 12. Nanotechnology for Cancer Biomarkers.
Keywords: Tumor markers; Cancer; Cancer-Treatment.; Nanomedicine; Tumour Biomarkers; Cancer Biology; Cancer Therapy; Cancer Nanotechnology